Analysing the Effects of Sales Stand Installations on Evacuation Dynamics in Indoor Sports Blocks - Ji Hun Kim; Kyung Hee Lee; Jun Gi Lee (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
Indoor sports clubs, gymnasiums, and sports blocks and complexes have the potential for causing significant casualties in the event of a fire. As a result, there is a significant amount of research being done on fire safety. The impact of sales stands on fire safety is a vital aspect that needs to be considered to ensure comprehensive safety measures. This study seeks to assess the effect of sales stands on the time it takes to evacuate indoor sports blocks in the event of a fire. A fire and evacuation simulation programme were utilised to analyse the characteristics of fire and evacuation. The findings indicated that the sales stand had an impact on the time it took for sports athletes and physical workers to complete the evacuation, particularly when the corridor width was wide. However, there was no significant effect observed when the hallway width was narrow. Instead, they expanded the congested area in the hallway, resulting in a longer resolution time. It is evident that sales stand in indoor sports blocks and sports centres or complexes could potentially jeopardise evacuation safety. This study can serve as a basis for implementing safety measures. It examines how obstacles in corridors, such as those found in schools and hotels, impact the evacuation behaviour of individuals. These findings are particularly relevant for indoor sports facilities, which share similar spatial characteristics.